The preparation of " salicylic acid azo 2,2,4,4 tetrahydroxybenzophenon" dye using Dowex in the acidic form as a catalyst - Ammar A. Dawood; Emaad M. Awsaj; Alaa S. Ateaa (Tikrit Journal of Pure Science, 2023)
The preparation of azo dye derivative from " p- amino Salicylic acid " through preparation diazonium salt from aromatic amine followed by coupling reaction with (2,2,4,4-tetrahydroxybenzophenonto) was carried out to give (salicylic acid azo 2,2,4,4 tetrahydroxybenzophenon) using Dowex in the acidic form as a catalyst. The structure of azo dye produced by this reaction was assigned on the bases of spectral data (FT-IR) and (C.H.N.) analysis and the results obtained indicated the occurrence of the coupling reaction by the novel acidic catalyst.